ANALISIS KUALITAS TENAGA KERJA KONTRAKTOR PELAKSANA PROYEK IRIGASI DI KABUPATEN KAPUAS - Sjaiful Bahri (INFO-TEKNIK, 2013)
Efforts to improve the quality of labor contractors is an important requirement given the challenges faced by contractors and also competition among contractors increasingly competitive as it is today. The quality and capabilities of the workforce is affected by the level of education, training, motivation, work ethic, mental and physical capabilities of the workforce concerned. As well as the work undertaken irrigation projects in Kapuas, where the project is a priority in improving agricultural resources. During this time the quality of irrigation works that have been produced showing the quality that has not been in accordance with the desired quality standards.Issues to be addressed in this study is the extent to which the quality of labor in irrigation work in Kapuas terms of factors knowledge of the work, quality of work, productivity, adaptability and flexibility, initiative and problem solving, cooperation and collaboration, reliability and accountability as well as the ability communicate and interact. Interest expressed in this research is to determine which factors are having a category that did not meet expectations and fulfill expectations and how big the achievement of quality work foreman and the foreman.The research methodology used to analyze other factors (sequence factors) were analyzed using Zero-one method to determine the weight of each variable to be implemented into the work quality assessment score calculation foreman and the foreman. Work quality on average across the head mason of all factors having an average total score of 312.27 (61.93%) in the category of classified work quality meets expectations. As for each personal foreman 6 (six) people classified as the quality of work meets expectations (over 60%), the remaining two (2) people classified work quality needs improvement. Work quality on average throughout the foreman on all the factors having an average total score of 320.53 (63.92%) in the category of classified work quality meets expectations. 300 (>60%). ">As for personal foreman each four (4) people are all classified work quality meets expectations or with a total average score of> 300 (> 60%).